2014
DOI: 10.4308/hjb.21.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Pachybasin, a Major Metabolite from Culture Broth of Endophytic Coelomyceteous AFKR-18 Fungus isolated from a Yellow Moonsheed Plant, Arcangelisia flava (L.) Merr.

Abstract: Endophytic fungi have been known to produce a broad range of biologically active secondary metabolites. One endophytic filamentous fungus, Coelomycetes AFKR-18, isolated from the young stems of a yellow moonsheed plant, Arcangelisia flava, has been found to produce pachybasin when placed in a liquid medium. The chemical structure of pachybasin was deduced from MS, 1D-, 2D-NMR spectrum analysis, and from reference data. On a micro-dilution test, pachybasin showed antimicrobial activities against E. coli, B. sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Yellow solid; R f ( n -hexane:EtOAc, 1:1) 0.87; IR (ATR) v max 1672, 1637, 1591, 1361, 1276, 1223, 757, 710 cm −1 ; 1 H-NMR (400 MHz, CDCl 3 ) δ 12.58 (1H, s, OH), 8.32–8.29 (2H, m, H-5, H-8), 7.82–7.79 (2H, m, H-6, H-7), 7.67 (1H, d, J = 1.2 Hz, H-4), 7.12–7.10 (1H, m, H-2), 2.47 (3H, s, H 3 -11); 13 C-NMR (100 MHz, CDCl 3 ) δ 188.3 (C-9), 182.9 (C-10), 162.9 (C-1), 148.8 (C-3), 134.6 (C-6), 134.3 (C-7), 133.8 (C-10a), 133.5 (C-8a), 133.3 (C-4a), 127.5 (C-5), 127.0 (C-8), 124.3 (C-2), 121.0 (C-4), 114.3 (C-9a), 22.4 (C-11) ( 1 H-NMR data agreed with literature) [ 10 ]; (+)−HRESIMS m / z 261.0529 [M + Na] + (calcd C 15 H 10 O 3 Na, 261.0528).…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Yellow solid; R f ( n -hexane:EtOAc, 1:1) 0.87; IR (ATR) v max 1672, 1637, 1591, 1361, 1276, 1223, 757, 710 cm −1 ; 1 H-NMR (400 MHz, CDCl 3 ) δ 12.58 (1H, s, OH), 8.32–8.29 (2H, m, H-5, H-8), 7.82–7.79 (2H, m, H-6, H-7), 7.67 (1H, d, J = 1.2 Hz, H-4), 7.12–7.10 (1H, m, H-2), 2.47 (3H, s, H 3 -11); 13 C-NMR (100 MHz, CDCl 3 ) δ 188.3 (C-9), 182.9 (C-10), 162.9 (C-1), 148.8 (C-3), 134.6 (C-6), 134.3 (C-7), 133.8 (C-10a), 133.5 (C-8a), 133.3 (C-4a), 127.5 (C-5), 127.0 (C-8), 124.3 (C-2), 121.0 (C-4), 114.3 (C-9a), 22.4 (C-11) ( 1 H-NMR data agreed with literature) [ 10 ]; (+)−HRESIMS m / z 261.0529 [M + Na] + (calcd C 15 H 10 O 3 Na, 261.0528).…”
Section: Methodssupporting
confidence: 84%
“…The structures of the other four known compounds were identified as taiwapyrone ( 3 ), xylariolide D ( 4 ), pachybasin ( 5 ), and N -(5-hydroxypentyl)acetamide ( 6 ) by comparison of NMR data with literature [ 5 , 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…endophytic in Salsola oppostifolia [184]. Finally, pachybasin has been also reported from an unidentified strain from the yellow moonshed (Arcangelisia flava) [185].…”
Section: Xanthones and Quinonesmentioning
confidence: 93%
“…The known compound 5 (pachybasin) was ever reported as a fungicide and showed significant inhibition activity against F. oxysporum with an MIC value of 16.0 μg/mL. 31 However, we found that the pachybasin had no antifungal activities against mycelial growth and spore germination of FOC under the concentration of 50 μg/ml. In addition, it was reported that harzianone (4) did not show antifungal activity against F. oxysporum at 30 μg/disc.…”
Section: ■ Discussionmentioning
confidence: 60%